The Influence of Human Resource Quality and Training on Performance of Personnel of the Directorate of Prevention of Special Detaction 88 Anti-Terror of the Police of the Republic of Indonesia - Muhammad Audi Aqshal Afandi; Kemal Taufik; Suhardi Suhardi (Dinasti Publisher, 2026)
This study aims to analyze the extent to which Human Resources (HR) Quality and Training influence Personnel Performance, both partially and simultaneously, on personnel of the Indonesian National Police's Special Detachment 88 Anti-Terror Prevention Directorate. The focus of this study is to examine whether improving HR competency quality and implementing effective training can significantly contribute to improving the performance of personnel who have strategic duties in preventing acts of terrorism. The type of research used is quantitative research, namely research that emphasizes the analysis of numerical data as a basis for drawing conclusions. However, this study also utilizes qualitative data as support, such as statements in questionnaires, consultation results, and short interviews between researchers and related informants. The study population includes 60 personnel, while the number of respondents who participated is the entire population, namely 60 people. Hypothesis testing was conducted using Structural Equation Modeling–Partial Least Square (SEM–PLS) software version 4.0 to determine the strength of the relationship between variables. The test results show that Human Resource Quality (X1) and Training (X2) partially have a positive and significant influence on Personnel Performance (Y). Thus, the better the quality of Human Resources and the more effective the training provided, the higher the resulting personnel performance. The R-Square test result of 0.423 indicates that 42.3% of the variation in Personnel Performance can be explained by Human Resource Quality and Training. Meanwhile, the remaining 57.7% is influenced by other factors outside this research model. These results emphasize the importance of improving the quality of human resources and training as a strategic effort to support the optimal performance of Densus 88 personnel